Penentuan Waktu Panen untuk Produksi Benih Bermutu Tanaman Kacang Panjang (Vigna sinensis L.) - MAYUN, IDA AYU; ASTININGSIH, A.A. MADE; SEDANA, I WAYAN; RAKA, I GUSTI NGURAH (Agrotrop : Journal on Agriculture Science; Vol 11 No 1 (2021)DO - 10.24843/AJoAS.2021.v11.i01.p03, 2021)
Determination of Harvest Time for Quality Seed Production of Long Bean Plants ( Vigna sinensis L.). Seed maturity generally occurs at the same time as fruit maturity. When the fruit reaches its physiological level, it is the best time to get seeds with high quantity and best quality. Early harvest before physiological maturity many seeds have not been completely filled so that they will produce low quality seeds because many seeds are wrinkled. Meanwhile, when harvested after physiological maturity, the seeds experience weather conditions so that many seeds experience physical and physiological quality deterioration. The research aimed to get the right harvest time in the production of quality seeds of long bean plants. This study used a randomized block design with 6 treatments at harvest pods after blooming and 4 replications. The six treatments were harvest age 14, 17, 20, 23, 26, and 29 days after the flowers bloom. The results showed that the right time to harvest pods for the production of long bean seeds was 26 days after blooming, the color of the pods has changed from green to yellow,  the seeds have the highest dry weight (7,56 g),  the best germination capacity (100%), and maximum vigor (88,78%).